Potret Perempuan Pesisir Madura Dalam Simbolisasi Makna Tradisi Lamaran Tunangan - Sri Rahayu; Ersa Alami (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
The objective of this research is to identify and analyze the symbolic meanings within the sequence of engagement proposal traditions in Madura. This study employs a qualitative method with a descriptive design. Data sources for this research include the observation of engagement proposal traditions and informants who possess deep knowledge of these practices. The data consists of the results from analyzing symbolic meanings derived from interviews and observations. The findings of this study identified 26 data points representing Madurese culinary items used as wedding offerings (seserahan kemanten) within the engagement tradition, analyzed through the lens of Roland Barthes' semiotic theory.